TRANSFORMASI SPIRITUALITAS GEREJA DAN NILAI-NILAI KEKRISTENAN DALAM KONTEKS PELAYANAN DIGITAL BERBASIS TEOLOGI PRAKTIS KONTEKSTUAL - Yohanes Twintarto Agus Indratno (Manna Rafflesia, 2026)
Rapid developments in information technology have brought about significant changes in various aspects of human life, including in the practice and expression of church life. Churches that were once centred on physical gatherings now face the challenge of adapting to the dynamics of digital ministry without losing their spiritual essence. This shift requires a new understanding of how Christian values can be authentically lived and realised in a fast-paced and interactive digital space. The emergence of digital churches shows that faith and technology can go hand in hand within a contextual practical theology framework. This study aims to analyse the transformation of church spirituality and how Christian values are recontextualised in digital ministry. The research method used is a qualitative approach with theological literature analysis. It can be concluded that the reconstruction of Christian spirituality in the digital age requires a reflective, critical, and contextual practical theological approach. The digital transformation of the church is not merely technological, but also ecclesiological, as it reshapes the way faith communities relate, worship, and witness. Digital ecclesiology opens up opportunities for the formation of inclusive and participatory faith communities, but at the same time presents challenges to spiritual depth, authenticity of relationships, and spiritual discipline. Therefore, the church needs to manage digital spirituality theologically, ethically, and responsibly.